Closer to fine: Surviving interactions between Hawaiian honeycreepers and a critically endangered aster - Jonah Dominguez; Timothy Chambers; Austen Elizabeth Conlon; Kapua Kawelo; Walter Thomas Russell; Autumn Bush; Jinelle Sperry (Biological Conservation, 2026)

Relationships among peri-traumatic circulating endocannabinoids and long-term, negative outcomes following traumatic injury - Emily A. Albertina; Carissa W. Tomas; Timothy J. Geier; Sydney C. Timmer-Murillo; Isela G. Pina; Kelley Jazinski-Chambers; Garrett Sauber; Jacklynn M. Fitzgerald; Christine L. Larson; Terri A. deRoon-Cassini; Cecilia J. Hillard (Psychopharmacology, 2026)
Rationale Traumatically injured individuals can develop chronic negative psychological sequelae. Improved understanding of contributing, peri-traumatic risk factors is essential to reduce the risk of these consequences. Previous studies have found that peri-traumatic, circulating endocannabinoid concentrations are positively associated with development of post-traumatic stress disorder (PTSD), chronic pain and depression months later, particularly in members of racial/ethnic groups that have been historically marginalized. Objectives This replication study examined relationships among peri-trauma serum endocannabinoid concentrations and long-term consequences in a cohort comprised primarily of individuals from marginalized racial and ethnic groups. Methods Participants ( n = 100; 81% from marginalized racial and ethnic groups) were traumatically injured adults presenting to the ED of an urban tertiary care hospital. Endocannabinoids N -arachidonoylethanolamine (AEA) and 2-arachidonoylglycerol (2-AG) were measured in serum collected within days (peri-trauma) and 6–10 months following injury (follow-up). Assessments, including PTSD, depression, pain and quality of life were completed. Statistical approaches, including multivariate, hierarchical regressions, were used to determine associations among serum endocannabinoid concentrations and long-term outcomes. Results Although it did not survive correction for multiple comparisons, peri-trauma serum 2-AG concentrations. Peri-trauma serum 2-AG concentrations were also positively associated with PTSD, pain severity, and functional engagement scores at follow-up. There were no significant associations between circulating 2-AG or AEA and depression. Conclusions These findings generally replicate earlier studies demonstrating that serum 2-AG concentrations are biomarkers of risk for PTSD and pain and uncover an additional association with poor functional quality of life. Further studies are needed to determine the underlying mechanisms of these relationships.

Identifying predictors of translocation success in rare plant species - Joe Bellis; Oyomoare Osazuwa‐Peters; Joyce Maschinski; Matthew J. Keir; Elliott W. Parsons; Thomas N. Kaye; Michael Kunz; Jennifer Possley; Eric Menges; Stacy A. Smith; Daniela Roth; Debbie Brewer; et al. (Conservation Biology, 2024)
The fundamental goal of a rare plant translocation is to create self‐sustaining populations with the evolutionary resilience to persist in the long term. Yet, most plant translocation syntheses focus on a few factors influencing short‐term benchmarks of success (e.g., survival and reproduction). Short‐term benchmarks can be misleading when trying to infer future growth and viability because the factors that promote establishment may differ from those required for long‐term persistence. We assembled a large ( n = 275) and broadly representative data set of well‐documented and monitored (7.9 years on average) at‐risk plant translocations to identify the most important site attributes, management techniques, and species’ traits for six life‐cycle benchmarks and population metrics of translocation success. We used the random forest algorithm to quantify the relative importance of 29 predictor variables for each metric of success. Drivers of translocation outcomes varied across time frames and success metrics. Management techniques had the greatest relative influence on the attainment of life‐cycle benchmarks and short‐term population trends, whereas site attributes and species’ traits were more important for population persistence and long‐term trends. Specifically, large founder sizes increased the potential for reproduction and recruitment into the next generation, whereas declining habitat quality and the outplanting of species with low seed production led to increased extinction risks and a reduction in potential reproductive output in the long‐term, respectively. We also detected novel interactions between some of the most important drivers, such as an increased probability of next‐generation recruitment in species with greater seed production rates, but only when coupled with large founder sizes. Because most significant barriers to plant translocation success can be overcome by improving techniques or resolving site‐level issues through early intervention and management, we suggest that by combining long‐term monitoring with adaptive management, translocation programs can enhance the prospects of achieving long‐term success.

Combined electrical resistivity tomography and ground penetrating radar to map Eurasian badger (Meles Meles) burrows in clay-rich flood embankments (levees) - Adrian White; Paul Wilkinson; James Boyd; James Wookey; John Michael Kendall; Andrew Binley; Timothy Grossey; Jonathan Chambers (Engineering Geology, 2023)

White matter tract conductivity is resistant to wide variations in paranodal structure and myelin thickness accompanying the loss of Tyro3: an experimental and simulated analysis - Farrah Blades; Jordan D. Chambers; Timothy D. Aumann; Christine T. O. Nguyen; Vickie H. Y. Wong; Andrea Aprico; Eze C. Nwoke; Bang V. Bui; David B. Grayden; Trevor J. Kilpatrick; Michele D. Binder (Brain Structure and Function, 2022)

Ertapenem for osteoarticular infections in obese patients: a pharmacokinetic study of plasma and bone concentrations - Jonathan Chambers; Madhu Page-Sharp; Sam Salman; John Dyer; Timothy M. E. Davis; Kevin T. Batty; Laurens Manning (European Journal of Clinical Pharmacology, 2019)

Evaluating centralized technical assistance as an implementation strategy to improve cancer prevention and control - Sarah Moreland-Russell; Prajakta Adsul; Seif Nasir; Maria E. Fernandez; Timothy J. Walker; Heather M. Brandt; Robin C. Vanderpool; Meagan Pilar; Paula Cuccaro; Wynne E. Norton; Cynthia A. Vinson; David A. Chambers; et al. (Cancer Causes & Control, 2018)

Experiments with By-Catch Reduction Devices to Exclude Diamondback Terrapins and Retain Blue Crabs - Andrew D. Corso; Jacqueline C. Huettenmoser; Olivia R. Trani; Kory Angstadt; Donna Marie Bilkovic; Kirk J. Havens; Timothy M. Russell; David Stanhope; Randolph M. Chambers (Estuaries and Coasts, 2017)

Iron and Pyritization in Wetland Soils of the Florida Coastal Everglades - Paul Julian; Randy Chambers; Timothy Russell (Estuaries and Coasts, 2017)

Riparian Ecosystems in the 21st Century: Hotspots for Climate Change Adaptation? - Samantha J. Capon; Lynda E. Chambers; Ralph Mac Nally; Robert J. Naiman; Peter Davies; Nadine Marshall; Jamie Pittock; Michael Reid; Timothy Capon; Michael Douglas; Jane Catford; Darren S. Baldwin; et al. (Ecosystems, 2013)

Molecular mechanisms of metastasis - Dave S. B. Hoon; Minoru Kitago; Joseph Kim; Takuji Mori; Adriano Piris; Katherine Szyfelbein; Martin C. Mihm; S. David Nathanson; Timothy P. Padera; Ann F. Chambers; Sharon A. Vantyghem; Ian C. MacDonald; et al. (Cancer and Metastasis Reviews, 2006)

Osteopontin and colon cancer progression - Timothy J. Yeatman; Ann F. Chambers (Clinical & Experimental Metastasis, 2003)

Land–atmosphere energy exchange in Arctic tundra and boreal forest: available data and feedbacks to climate - Werner Eugster; Wayne R Rouse; Roger A. Pielke Sr; Joseph P. Mcfadden; Dennis D Baldocchi; Timothy G. F Kittel; F. Stuart Chapin; Glen E. Liston; Pier Luigi Vidale; Eugene Vaganov; Scott Chambers (Global Change Biology, 2000)
Summary This paper summarizes and analyses available data on the surface energy balance of Arctic tundra and boreal forest. The complex interactions between ecosystems and their surface energy balance are also examined, including climatically induced shifts in ecosystem type that might amplify or reduce the effects of potential climatic change. High latitudes are characterized by large annual changes in solar input. Albedo decreases strongly from winter, when the surface is snow‐covered, to summer, especially in nonforested regions such as Arctic tundra and boreal wetlands. Evapotranspiration ( Q E ) of high‐latitude ecosystems is less than from a freely evaporating surface and decreases late in the season, when soil moisture declines, indicating stomatal control over Q E , particularly in evergreen forests. Evergreen conifer forests have a canopy conductance half that of deciduous forests and consequently lower Q E and higher sensible heat flux ( Q H ). There is a broad overlap in energy partitioning between Arctic and boreal ecosystems, although Arctic ecosystems and light taiga generally have higher ground heat flux because there is less leaf and stem area to shade the ground surface, and the thermal gradient from the surface to permafrost is steeper. Permafrost creates a strong heat sink in summer that reduces surface temperature and therefore heat flux to the atmosphere. Loss of permafrost would therefore amplify climatic warming. If warming caused an increase in productivity and leaf area, or fire caused a shift from evergreen to deciduous forest, this would increase Q E and reduce Q H . Potential future shifts in vegetation would have varying climate feedbacks, with largest effects caused by shifts from boreal conifer to shrubland or deciduous forest (or vice versa) and from Arctic coastal to wet tundra. An increase of logging activity in the boreal forests appears to reduce Q E by roughly 50% with little change in Q H , while the ground heat flux is strongly enhanced.